The accuracy of renal point of care ultrasound to detect hydronephrosis in children with a urinary tract infection. (April 2015) - Guedj, Romain; Escoda, Simon; Blakime, Philippe; Patteau, Géraldine; Brunelle, Francis; Cheron, Gérard
<x xml:space="preserve">Abstract</x> The objective of this study was to investigate the accuracy of renal point of care ultrasound (POCUS) for the detection of hydronephrosis in children with a urinary tract infection (UTI). We prospectively included all patients with a final diagnosis of UTI who visited our pediatric emergency department between November 2009 and April 2011. Emergency physicians were encouraged to perform a renal POCUS during these visits, and a follow-up renal ultrasonography was performed by a radiologist who was blinded to the results of POCUS. We calculated the accuracy of POCUS to detect hydronephrosis (renal pelvis enlargement ≥10 mm). We included 433 UTI visits, and 382 (88.2%) POCUS were performed. The sensitivity and the specificity were 76.5% (95% confidence interval: 58.1–94.6%) and 97.2% (95.2–99.2%), respectively. The positive and the negative predictive values were 59.1% (36.4–79.3%) and 98.8% (97.7–99.9%), respectively. Renal POCUS might be used to rule out hydronephrosis in pediatric UTI.